2016
DOI: 10.1177/1729881416666777
|View full text |Cite
|
Sign up to set email alerts
|

A rough concrete wall-climbing robot based on grasping claws

Abstract: Climbing robots have been widely used to inspect smooth walls. However, a good adsorption method has not been found for the inspection of a cliff surface and a dusty high-altitude surface with small vibration, both of which are made of coarse concrete, square brick, or rock. In this article, first, we analyzed the bionic structure of the cockroach legs and observed their morphological characteristics of the spiny claws on these legs. We also studied the interaction theory of the bionic claw with the bulges on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Secondly, our findings largely corroborate earlier observations of claw shape made in other lizard taxa (Zani 2000;D'Amore et al 2018;Yuan et al 2018;but Crandell et al 2014), birds (Birn-Jeffery et al 2012but Pike and Maitland 2004) and mammals (Tulli et al 2016), in that climbing species occupying vertical elements carry short, strongly curved, full-bodied claws. Biomechanical and experimental work showed that claws of such shape have a high mechanical strength and improve clinging performance on rough surfaces by increasing frictional grip (Zani 2000;Dai et al 2002;Provancher et al 2005;Tulli et al 2011;Xu et al 2016), which suggests that carrying short, strongly curved, full-bodied claws is an adaptation for efficient locomotion on vertical elements (Zani 1999). Interestingly, our data also shows that climbing species have less thick claws (relative to body size) than ground-dwelling species.…”
Section: Claw Shape Adaptations For Efficient Locomotion On Disparatementioning
confidence: 99%
“…Secondly, our findings largely corroborate earlier observations of claw shape made in other lizard taxa (Zani 2000;D'Amore et al 2018;Yuan et al 2018;but Crandell et al 2014), birds (Birn-Jeffery et al 2012but Pike and Maitland 2004) and mammals (Tulli et al 2016), in that climbing species occupying vertical elements carry short, strongly curved, full-bodied claws. Biomechanical and experimental work showed that claws of such shape have a high mechanical strength and improve clinging performance on rough surfaces by increasing frictional grip (Zani 2000;Dai et al 2002;Provancher et al 2005;Tulli et al 2011;Xu et al 2016), which suggests that carrying short, strongly curved, full-bodied claws is an adaptation for efficient locomotion on vertical elements (Zani 1999). Interestingly, our data also shows that climbing species have less thick claws (relative to body size) than ground-dwelling species.…”
Section: Claw Shape Adaptations For Efficient Locomotion On Disparatementioning
confidence: 99%
“…The maximum top size of the micro-hook is derived from Reference [21]. The top size of the micro-hook should be lower than the maximum size.…”
Section: Calculation Of Hook Top Sizementioning
confidence: 99%
“…Additionally, innovative soft climbing robots include lightdriven [24,25] and magnetism-driven soft robots [26,27]; energy-storage hopping robots imitating a locust and a flea [28,29], soft grappling mechanisms [30][31][32][33], walking robots inspired by crawling of multi-legged beetles [34], and rolling robots are available [35]. Compared with current rigid and flexible climbing robots [36][37][38][39][40], the aforementioned soft climbing robots [41,42] show stronger deformability and more user-friendly human-computer interaction.…”
Section: Introductionmentioning
confidence: 99%